PKM PENYULUHAN PENDIDIKAN KARAKTER SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN MEDIA SOSIAL DAN JEJARING SOSIAL DI KALANGAN REMAJA - Tahir, Heri; Heri, Ririn Nurfaathirany; Satrul, Hairul Saleh; Patmawati, Susi Anita; Junaeda, St (Universitas Negeri Makassar, 2024)
The development of juvenile delinquency and crime is no longer limited to physical, but also extends to cybercrime, terror and crime committed through social media and other electronic media, so that it becomes a special concern to be able to make prevention efforts through social media. From the many cases of cyberbullying in Indonesia, the Indonesian Child Protection Commission (KPAI) stated that most cyberbullying actions or behaviors are carried out by children and adolescents, because of the data obtained, from 253 cases of bullying, there were 122 children who were victims of cyberbullying and 131 children became perpetrators of cyberbullying itself seeing the development of technology and juvenile delinquency through social media and social networks, it is considered important to provide counseling to the younger generation, especially regarding Character Education as an Effort to Prevent Misuse of social media and social networks among Adolescents.Providing information related to criminal sanctions for misuse of social media and social networks among Adolescents is also important to be socialized so that it is hoped that adolescents can become agents of change in socializing media positively. Based on the evaluation results of the extension activities in the context of implementing Community Service activities, it can be concluded that this activity is considered successful and successful. This activity is said to be successful because it can be seen from the participants who are expected to attend exceeding the target, namely above 150 participants, and exceeding the capacity of the facilities provided. Seeing the enthusiasm of the participants who attended, this activity is considered very interesting and needed by educational units. The quiz activity carried out as the closing of the activity showed an increase in student and teacher knowledge related to the material provided.